Historical Analysis of the Islamic Fiscal Policies of Fatimid Egypt, Mamalik, Safavid Persia, and Mughol India - Dodi Yarli; Yadi Janwari; Sofyan Al-Hakim (al-Afkar, Journal For Islamic Studies, 2024)
The history of fiscal policy in Islam during the Fatimid and Mamaalik periods in Egypt, the Syafawiyah in Persia, and the Mughals in India, can be divided into two main phases: the glory phase and the decline phase. In the glory phase, historical records show that fiscal management under the governments of these caliphates generated revenue surpluses. This situation contributes to the country's economic stability and security. The Fatimids, Mamaaliks, Syafawiyahs, and Mughols in India implemented fiscal policies that encouraged increasing state income from diverse sectors such as agriculture, trade, and industry. The state's largest sources of income come from taxes, tīmār, muḳāṭa'a, waqf and ghanimah. High income is used to support the country's progress through financing territorial expansion, infrastructure development, education and health. However, during the decline phase, the Fathimiyah, Mamaalik, Syafawiyah and Mughol experienced budget deficits. Decreasing state income, failure to westernize the economy, high war costs, and high state debt are factors causing deficits in their fiscal policy.